The Implementation Of Analytical Hierarchy Process (AHP) Method In Selecting Outstanding Students - Masita, Yeti; Siswanto, Siswanto; Alinse, Rizka Tri (Jurnal Media Computer Science, 2025)
SD Negeri 12 Central Bengkulu is one of the public elementary schools in Central Bengkulu Regency, Bengkulu Province. At SD Negeri 12 Bengkulu, every academic year an assessment of students is carried out through several criteria to select outstanding students who have the ability to master lessons and good self-ethics. The implementation of Analytical Hierarchy Process (AHP) method in the selection of outstanding students at SD Negeri 12 Central Bengkulu can help provide information in the form of recommendations for selecting outstanding students at school based on the final results of AHP method, and can help homeroom teachers in determining outstanding students by looking at the assessment aspects of report cards, attitude scores, percentage of student attendance, and academic and non-academic achievements obtained by students. From the sample data of student assessments at SD Negeri 12 Central Bengkulu, used for calculations through the Analytical Hierarchy Process (AHP) Method for the 2023/2024 academic year as many as 10 students, the recommended ranking results for outstanding students who are in the top 3 are Daffa Hidayatullah, Aura Despianty, and Ciko Pandu Wiryo. Based on the black box testing that has been carried out, the results show that the functionality of the implementation of Analytical Hierarchy Process (AHP) method in selecting outstanding students at SD Negeri 12 Central Bengkulu runs as expected and the application is able to display the results of recommendations for selecting outstanding students through AHP method stages. Based on the alpha testing, the results obtained that the application is quite interesting and quite helpful in selecting outstanding students in each class at SD Negeri 12 Central Bengkulu.